1998
DOI: 10.2337/diabetes.47.6.890
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic corticotropin-releasing hormone is a mediator of the anorexigenic effect of leptin.

Abstract: Leptin, ob gene product, inhibits feeding behavior and stimulates energy expenditure in rodents. Corticotropin-releasing hormone (CRH) and neuropeptide Y (NPY), which act in the hypothalamus to influence energy homeostasis, may mediate the anorexic effect of leptin. The present studies were undertaken to examine the possible involvement of hypothalamic CRH in the anorexigenic action of leptin in male Wistar rats. Recombinant leptin (2 microg/rat), microinjected into the third ventricle, inhibited food intake a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
83
0
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 171 publications
(87 citation statements)
references
References 0 publications
3
83
0
1
Order By: Relevance
“…Both in vivo and in vitro studies have shown that leptin increases expression of CRF in the hypothalamus [12,28,43,54]. In fact, simultaneous injection of leptin and a non-specific CRF receptor antagonist confirmed that a ligand for CRF receptor contributes to leptin's anorectic effect [21,59].…”
Section: Discussionmentioning
confidence: 96%
“…Both in vivo and in vitro studies have shown that leptin increases expression of CRF in the hypothalamus [12,28,43,54]. In fact, simultaneous injection of leptin and a non-specific CRF receptor antagonist confirmed that a ligand for CRF receptor contributes to leptin's anorectic effect [21,59].…”
Section: Discussionmentioning
confidence: 96%
“…CRH has also been shown to mediate the anorexigenic effects of leptin (32). Besides having anorexigenic effects, CRH has been shown to increase sympathetic nerve activity in brown adipose tissue involved in the control of thermogenesis (6) and also to mediate leptin actions on the expression of uncoupling protein mRNA in this tissue (33).…”
Section: Discussionmentioning
confidence: 99%
“…When delivered icv, urocortin (177) and urocortin II (144) produce greater intake suppression and fewer stress-related responses than does CRH. The contemporary model has assigned a role for CRH in the mediation of leptin effects (156,188,192). Thus, CRH 2a -R mRNA, CRH mRNA, and peptide level are increased after icv leptin administration (132,145,192), and treatment with a CRH-R antagonist attenuates the intake suppression that otherwise follows icv leptin administration (64,188).…”
Section: Crh/urocortinmentioning
confidence: 99%
“…The contemporary model has assigned a role for CRH in the mediation of leptin effects (156,188,192). Thus, CRH 2a -R mRNA, CRH mRNA, and peptide level are increased after icv leptin administration (132,145,192), and treatment with a CRH-R antagonist attenuates the intake suppression that otherwise follows icv leptin administration (64,188). The mediating mechanisms for these actions (with possibilities involving, for example, Ob-Rb on CRH neurons and projections to PVN from arcuate neurons containing POMC, CART, AgRP, and NPY (e.g., 85,42) are yet to be established.…”
Section: Crh/urocortinmentioning
confidence: 99%
See 1 more Smart Citation